The Gadjah Mada Stroke Algorithm Scoring System (ASGM) and Guy's Hospital Stroke Score (GHSS) in Determining the Type of Stroke Emergency as A Substitute for the CT-Scan in the Emergency Room - Mohtar, M Sobirin; Tjomiadi, Cynthia Eka Fahyuning; Apriannor, Ahmad (Poltekkes Kemenkes Semarang, 2024)
Background: Nurses need a diagnostic tool in the form of a simple scoring system including the Gadjah Mada Stroke Algorithm (ASGM) and Guy's Hospital Stroke Score (GHSS) in determining the type of stroke and preventing delays.Purpose: Analyzing the comparison of the ASGM and GHSS scoring systems in determining the type of stroke emergency.Methods: This research method was a quantitative pre-experimental design (posttest only design). The population was all stroke patients in the emergency room with 30 samples and the sampling technique is accidental sampling. As for the stages for each respondent, an ASGM assessment was carried out which consisted of 3 components and GHSS 9 components. The statistical test used is the Paired Sample T-test.Results: Based on the results of the Paired Sample T-test was the value of Sig. of 0.000 <0.05. The average difference in the duration of determining the type of emergency and nursing diagnoses on the assessment system and ASGM and GHSS is 7.6 minutes. Furthermore, it also shows lower data of 7.066 and upper 8.134. This shows that the duration range for determining the type of emergency using ASGM is around 7.1 – 8.1 minutes faster compared to GHSS. Based on the accuracy test that ASGM has a sensitivity level of 86.66% and a specificity of 96.66%, while GHSS has a sensitivity level of 56.66% and a specificity of 63.33%.Conclusion: ASGM and GHSS assessment methods are effective in determining the type of emergency in stroke patients in the emergency department.